Facts, interests, and values: Identifying points of convergence and divergence for food systems - Deconinck, Koen (International Food Policy Research Institute, 2023)
Better policies offer significant potential to meet the challenges facing food systems, but policy reform has often proved difficult. This chapter argues that the difficulty lies in disagreements over facts, interests, and values—alone or in combination.¹ For Sunstein (2018), politically contentious issues “are fundamentally about facts rather than values,” and “[i]f we can agree on the facts, we should be able to agree on what to do—or at least our disagreements should be narrowed greatly.” By contrast, a considerable literature on political economy has long emphasized the importance of tensions between the public interest and special interests (Rausser et al. 2011), while a third perspective emphasizes the importance of (differences over) values (Thacher and Rein 2004; Inglehart and Welzel 2005; Stewart 2006; Enke 2020). In reality, all three are likely to play a role, although their relative importance will vary by issue.